DEFINITION OF NON-LETHAL WEAPON IN INTERNATIONAL LAW - Kurdyukov, Gennadiy; Drygina, Anastasia (Gênero & Direito, 2019)
This paper examines the terminology, reveals the definition of non-lethal weapon, provides a detailed analysis of the criteria for lethality of weapons, distinguishes between the concepts of non-lethal and lethal weapons, and non-lethal weapons are also separated from other items used as weapons. The international legal science also lacks the universally accepted definition of the non-lethal weapon concept. That is why the authors have paid attention to the question of terminology in relation to this weapon, as well as to the criteria on the basis of which it can be distinguished from other types.